Pengembangan BUMDES Bancangan Melalui Budidaya Maggot BSF Sebagai Alternatif Pakan Ternak - Yunaita Rahmawati; Umi Sarofah (Abdimas Indonesian Journal, 2022)
The purpose of establishing BUMDES is to encourage and accommodate all activities and increase community income, both those that develop according to local customs and culture as well as economic activities that are submitted to be managed by the community through central and local government programs or projects. as a village effort, the establishment of a Village-Owned Enterprise is really to maximize the potential of the village community, be it the economy of natural resources or human resources. however, development in the economic field of natural resources and human resources has not been carried out as much as possible. this is due to the difficulties experienced by the BUMDes managers who have not been optimal in maximizing the potential of the village of Bancangan, Sambit, Ponorogo. Armed with human resource assets in the form of BUMDes management who have qualified capabilities to carry out this activity in the long term. As well as the problem regarding household waste that has not been resolved, then the cultivation of BSF maggot as an animal feed saver is feasible. After the cultivation of maggot BSF, the BUMDes management can move to take advantage of the potential of nature and human potential to be developed.